Pendampingan Wisata Edukasi di Pusat Penelitian Perkebunan Gula Indonesia - Nisa Hafi Idhoh Fitriana; Ellecia Pricillia Siahaan; Nabilah Ainur Rohmah; Danang Permadhi (Lembaga Pengembangan Kinerja Dosen, 2024)
The Indonesian Sugar Plantation Research Center (P3GI) plays a crucial role in the development of the sugar industry in Indonesia. Currently, the contribution extends not only to the sugarcane industry but also begins to branch out into the field of education by providing educational tours for the public. The educational tourism activities at the Indonesian Sugar Plantation Research Center (P3GI) not only offer tours but also include accompaniment. The main objective of this accompaniment is to enhance tourists' knowledge by accompany and educating them during their visit to P3GI. Guides will take tourists through several educational spots, including the library, museum, explant area, garden, and plantation. After the tour, tourists are invited to taste natural sugarcane juice (STA). The outcomes of the educational tourism guidance activities at the Indonesian Sugar Plantation Research Center (P3GI) have beneficial effects for all parties involved, especially tourists.